A Cross-Sectional Assessment of Basal Cell Carcinoma Recurrence after Single-Stage Excision and Reconstruction in a Balochistani Population - Kamal Uddin Khan, Farzana Abdullah, Hifza Bashir, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The majority of non-melanoma skin cancers worldwide are basal cell carcinomas. While metastasis is not common with BCC, its spread within tissues and tendency to return cause a lot of concern for those treating it. The recurrence rate is affected by characteristics of the tumor, how far the excision is from the tumor edges, where the tumor is located and the way the area is reconstructed. Materials & Methods: A cross-sectional study conducted from June 2022 to January 2023. Histologically confirmed BCC, age ≥18 years, undergoing single-stage excision and reconstruction were included. Incomplete excision records, follow-up <6 months, immunosuppressed patients were excluded. Recurrence was defined as histologic confirmation of BCC at the same site. Results: Most tumors (85/120, 71%) were on sun-exposed sites of the head and neck (face 68%, scalp 3%), with 35% on the nose. Others involved the trunk (15%) or extremities (14%). Mean tumor diameter was 15.2 ± 6.8 mm. Surgical margins averaged 4.5 ± 1.2 mm. Final pathology showed clear margins in 108 cases (90%) and involved/close margins in 12 (10%). Reconstruction methods were: primary closure (n=60, 50%), local flap (36, 30%), and skin graft (24, 20%). Conclusion: Our study highlights an 8.3% recurrence rate of BCC post single-stage excision in the Balochistani population, with higher recurrence linked to positive margins, morpheaform subtype, and larger tumor size. Keywords: Basal Cell, Reoccurrence, Baluchistan, Single Stage Excision